PENGARUH EFEKTIVITAS SIA DAN PENGGUNAAN TEKNOLOGI INFORMASI PADA KINERJA INDIVIDUAL DENGAN INSENTIF KARYAWAN SEBAGAI PEMODERASI - Intan Fatmayoni, I Gusti Agung Ayu; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2017)
The role of incentives are expected to stimulate employee discipline to increase productivity and work performance of employees to achieve company goals. This research was conducted in Manufacturing Company Bad Ass Garment Factory. The purpose of research to find out the test results influence the effectiveness of the accounting information system and the use of information technology on the performance of individual employees with incentive as moderating. 52 samples selected by purposive sampling technique. The hypothesis is tested by using multiple linear regression analysis and moderation regression analysis. The result of the analysis is the level of effectiveness of the accounting information system and the use of information technology has positive influence on individual performance. Employee incentives could strengthen the influence of the effectiveness of information systems against individual performance incentives while the employee is not able to moderate the effect of the use of information technology to individual performance.
Keywords: Effectiveness of Accounting Information Systems, Information Technology Usage, Employee Incentives, Individual Performance